2019
DOI: 10.1186/s13068-019-1449-0
|View full text |Cite
|
Sign up to set email alerts
|

An actinobacteria lytic polysaccharide monooxygenase acts on both cellulose and xylan to boost biomass saccharification

Abstract: Background Lytic polysaccharide monooxygenases (LPMOs) opened a new horizon for biomass deconstruction. They use a redox mechanism not yet fully understood and the range of substrates initially envisaged to be the crystalline polysaccharides is steadily expanding to non-crystalline ones. Results The enzyme Kp LPMO10A from the actinomycete Kitasatospora papulosa was cloned and overexpressed in Escherichi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…To our knowledge, this pattern has not been previously reported. Possible exceptions are Tt LPMO10A, which contains a Tyr but was reported to have mixed C1/C4 activity [ 73 ], and Kp LPMO10A, which has a Trp and was reported to have both mixed regioselectivity and activity on both cellulose and chitin [ 107 ]. In addition, a similar trend was observed concerning the axial aromatic residue at the active site (Phe or Tyr) [ 103 , 108 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this pattern has not been previously reported. Possible exceptions are Tt LPMO10A, which contains a Tyr but was reported to have mixed C1/C4 activity [ 73 ], and Kp LPMO10A, which has a Trp and was reported to have both mixed regioselectivity and activity on both cellulose and chitin [ 107 ]. In addition, a similar trend was observed concerning the axial aromatic residue at the active site (Phe or Tyr) [ 103 , 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…We observed that whereas C1-active AA10 LPMOs contain an axial Phe (regardless of cellulose or chitin specificity), mixed C1/C4-active AA10 LPMOs possess a Tyr at this position. Again, the only exceptions to this pattern among characterized AA10 members are Tt LPMO10A and Kp LPMO10A [ 73 , 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…They are C1/ C4-specific for cellulose oxidation and C1-specific for chitin oxidation. Recently, a multifunctional LPMO10, KpLPMO10A has been reported that besides chitin-and cellulose-activity, it can also act on xylan to produce C4-oxidized products (Correa et al 2019). In addition, it is reported that, PaLPMO9H is C4-specific on mixedlinkage glucans, and C1/C4-specific on glucomannan (Fanuel et al 2017).…”
Section: Structures Of Substratesmentioning
confidence: 99%
“…The LPMOs are important for their auxiliary activity. It enhances the activity of Cellulase enzyme for degradation of cellulose and lignocelluloses (Corrêa et al 2019). The only identified AA16 family, the AaAA16 showed sequential synergistic effect with T. reesei CBHI on nano-fibrillated cellulose (NFC) and PASC.…”
Section: Synergistic Effect Of Aflpmo16mentioning
confidence: 99%